Interjections and Emotion (with Special Reference to "Surprise" and "Disgust"). (January 2014) - Goddard, Cliff
"All languages have 'emotive interjections' (i.e., interjections expressing cognitively based feelings)" (Wierzbicka 1999, p. 276)—and yet emotion researchers have invested only a tiny research effort into interjections, as compared with the huge body of research into facial expressions and words for emotion categories. This article provides an overview of the functions, meanings, and cross-linguistic variability of interjections, concentrating on non-word-based ones such as Wow!, Yuck!, and Ugh! The aims are to introduce an area that will be unfamiliar to most readers, to illustrate how one leading linguistic approach (natural semantic metalanguage [NSM]) deals with interjectional meaning, and to start a discussion about an interdisciplinary research agenda for the study of emotive interjections. Examples are drawn from English, Polish, and Cantonese.